Mapping Floral Genetic Architecture in Prunus mume, an Ornamental Woody Plant - Li, Mingyu; Sang, Mengmeng; Wen, Zhenying; Meng, Juan; Cheng, Tangren; Zhang, Qixiang; Sun, Lidan (Frontiers in Plant Science, 2022)
Floral traits are both evolutionarily and economically relevant for ornamental plants. However, their underlying genetic architecture, especially in woody ornamental plants, is still poorly understood. We perform mapping experiments aimed at identifying specific quantitative trait loci (QTLs) that control the size, shape, architecture, color, and timing of flowers in mei (Prunus mume). We find that the narrow region of chromosome 1 (5-15 Mb) contains a number of floral QTLs. Most QTLs detected from this mapping study are annotated to candidate genes that regulate various biological functions towards floral formation. We identify strong pleiotropic control on different aspects of flower morphology (including shape, petal number, pistil number, petal color, and calyx color) and flower timing, but find different genetic systems that mediate whether a flower produces pistils and how many pistils a flower produces. We find that many floral QTLs display pleiotropic effects on shoot length growth but shoot radial growth, implicating a possible association of floral display with light capture. We conduct a transcriptomic study to characterize the genomic signature of floral QTLs expressed in mei. Our mapping results about the genetic control of floral features make it promising to select superior varieties for mei carrying flowers of ornamental value.